The evolution of mastectomies in the oncoplastic breast surgery era - Zucca-Matthes, Gustavo [UNESP]; Manconi, Andrea [UNESP]; Viera, Rene Aloísio da Costa [UNESP]; Michelli, Rodrigo Augusto Depieri [UNESP]; Matthes, Angelo do Carmo Silva [UNESP] (Gland Surgery, 2013)
Over time, surgical techniques have advanced to the point where oncological safety and aesthetic outcomes are the pillars of contemporary breast surgery. Variations of mastectomy came up and started allowing the oncological safety and the possibility of an immediate breast reconstruction. Nowadays the association between plastic surgical techniques and mastectomy with immediate breast reconstruction is one of the best alternatives to treat breast cancer and also improved overall aesthetic outcomes and favors the achievement of contralateral breast symmetry. Oncoplastic mastectomy is a feasible term and can be routinely used.
Keywords: Breast cancer; Breast conserving treatment; Mammoplasty; Mastectomy; Reconstructive surgical procedure